The Implementation of Learning Motivation in Physical Education and Sports to Enhance Students' Spiritual Intelligence: An Islamic Law Approach - Arifuddin Usman; Muhammadong Muhammadong (Journal of Innovative and Creativity, 2025)
This research aims to explore the application of learning motivation in physical education and sports to elevate students' spiritual intelligence, viewed through the lens of Islamic law. The goal is to look into how motivation in physical education can be used to help students grow spiritually in line with Islamic principles. A qualitative methodology was utilized, incorporating a literature study and interviews with instructors and students. Thematic analysis was employed to discern essential components pertaining to motivation, physical education, sports, and spiritual intelligence. The findings indicate that the incorporation of Islamic ideals into physical education and sports fosters the development of both physical and spiritual qualities, including discipline, patience, and thankfulness. Teachers are very important for making sure that the learning environment follows Islamic rules. The study also shows that improving spiritual intelligence through physical exercises has a good effect on pupils' character and schoolwork. In conclusion, the research substantiates that motivation for learning in physical education and sports, rooted in Islamic law, significantly elevates students' spiritual intelligence and fosters their comprehensive growth.